Human rights law and corporate regulation a neo-concession approach - Barrett, Jonathan, 1962- (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
This book argues for an intensely humanist engagement with the company and presents a model of company regulation that is compatible with the protection, respect for and fulfilment of human rights. Dr Barrett provides a theoretical framing for corporate regulation in the context of human rights States. He argues that States which have ratified the fundamental human rights instruments should, on principle, exclude bodies corporate from the human rights ecosystem, except to the degree necessary to respect property rights of humans and human rights in business. He therefore develops a neo-concession' account of the corporation as the basis for a model of corporate regulation to protect human rights. The book outlines and recommends theprincipal features of a company under a neo-concession model, and the role of regulators in furthering the State's human right obligations. It also delves into the potential issues of technological developments, including decentralised autonomous organisations, and the lessons policymakers can gain from First Nations' approaches to business. This is athought-provoking volume that will appeal to scholars in the disciplines of human rights law and corporate governance, as well as policymakers and regulators interested in regulating business for greater societal good.
Keywords: Social responsibility of business -- Law and legislation; International business enterprises -- Law and legislation; Corporation law; Human rights -- Economic aspects; Concessions; LAW / Corporate; POLITICAL SCIENCE / Political Freedom & Security / Human Rights